AGE-RELATED MORPHOLOGICAL CHANGES OF THE MENISCI IN WOMEN (Global Conference on Medical and Health Sciences, 2026)
The menisci are essential fibrocartilaginous structures of the knee joint that play a critical role in load distribution, shock absorption, joint stabilization, lubrication, and protection of articular cartilage. Age-related degenerative processes significantly affect the morphology and functional properties of the menisci, particularly in women, due to hormonal changes, metabolic alterations, and biomechanical factors associated with aging. Understanding the morphological transformations occurring in the menisci throughout different stages of life is important for improving the diagnosis, prevention, and treatment of knee joint disorders.
Keywords: Meniscus, Women, Aging, Morphology, Knee Joint, Fibrocartilage, Degeneration, Histology, Osteoarthritis, Musculoskeletal Aging.